Localization of Escherichia coli rpoC Mutations That Affect RNA Polymerase Assembly and Activity at High Temperature - Nedea, Eduard C. (American Society for Microbiology, 1999)
We localized five rpoC (β′) mutations affecting Escherichia coli RNA polymerase assembly. The Ts4, XH56, and R120 mutations changed β′ residues conserved throughout eubacteria; the JE10092 mutation occurred in the hypervariable region; rpoC1 (TsX) changed a universally conserved residue and corresponds to yeast rpb1-1. Thus, distinct, predominantly conserved β′ residues participate in interactions holding RNA polymerase together.